Perlindungan Hukum Terhadap Pekerja Anak Dalam Transaksi Penjualan Koran di Kota Batam - Wulan Mei Firina (Journal of Law and Policy Transformation, 2020)
Indonesia’s constitution has been giving absolute protection regarding the employment and decent rights to live for its citizen. Based on that matter, the government and legislature worked together to legalize Law of Republic Indonesia Number 13 Year 2003 regarding Employment where there will be protection regarding the equality of opportunity, as well as the fair treatment for the workers. One of the aspects covered by this law is the welfare of child labor that is stated in article number 68 until 75. Article 68 has established that it is forbidden to employ child labor. Like any other cities in Indonesia, Batam is also partaking in this phenomenon that created a complex and problematic social issue. The objective of this research is to analyze the construction of the law that protects child labor, as well as the role of the media companies and the government in preventing this issue. The data has been collected by doing unstructured interviews and observation. The research is done in “Jurisdiction Sociologies” method. The result of the research shows that the jurisdiction commitment of the state is to protect the child labor through the construction of the law that prohibited underage children to work and even if they must, based on the provision of the norms, it is compulsory for them to receive a proper law protection. Media companies as the manufacturers of the newspaper have partaken in this illegal child labor. The governor officials in Batam should have gave the proper protection for the children, be it preventive or repressive.